Preliminary Studies on the Nutritional Requirements of Teak (Tectona grandis L.) - Bhatnagar, H. P.; Gupta, B. B.; Rauthan, B. S.; joshi, D. N. (Indian Forester, 1969)
Sand culture experiment was conducted on Teak (Tectona grandis) seedlings to study the mineral Nutrient requirements with respect to Nitrogen, Potassium and Phosphorus. Within the limitations of the experiment the results have indicated that for good growth, teak seedlings require about 680 mg/Plant of Nitrogen and Potassium and about 450 mg/Plant of Phosphorus. Results of the chemical analysis of the plant material have shown that higher application of Nitrogen and Phosphorus (680 mg/ Plant) increases the absorption of these minerals as well as of Calcium. and Magnesium by the plant tissues in comparison to lower (340 mg/Plant) application of Nitrogen and Phosphorus. As regards the application of Potassium the results have shown inverse correlation with respect to the absorption of Calcium. and .Magnesium by the plant tissues. Higher Potassium application (680 mg/Plant) has resulted in lower absorption of both Calcium and Magnesium. In respect of three element treatment combinations the data on ash percentage have indicated that higher Potassium application increases the ash percentage in the plant tissues.